Language of İnstruction and Cultural İdentity Formation in Public Secondary Schools in Azerbaijan - Samoilova, Lana (ADA University, 2024)
The study explores the role of the language of instruction in the process of cultural identity formation within the context of fresh graduates of public secondary schools in Azerbaijan. Predetermined by the post-colonial post-Soviet context, the Azerbaijani educational system still possesses a multilingual framework with two major mediums of instruction, Azerbaijani and Russian. While the state language as a medium of instruction is a standard feature, the utilization of the Russian language allegedly contributes to social dissatisfaction and heated debates. To explore the cultural aspect of the phenomenon, the study investigates the role of the language of instruction based on the perceptions of fresh graduates of public secondary schools currently pursuing their bachelor’s degrees in Azerbaijan. Guided by the Vygotskian sociocultural theory and the state policy of multiculturalism, the study explores the perceived effect of the language of instruction on the students’ values and beliefs. As a result of qualitative research conducted through a set of interviews with fresh high-school graduates of both language streams, the study shows that the students do not consider the language of instruction an important factor in their cultural identity development process. The study participants who were educated in Russian also do not culturally identify themselves as Russians. However, the findings demonstrate that there are still differences in the students’ cultural identity. The findings, however, establish particular dynamics between the language of instruction and cultural identity expressed through the features highlighted as characteristics of the students of different streams. The study contributes to the existing literature on mechanisms of cultural identity and the role of the language of instruction in the post-colonial and post-Soviet context of the modern Azerbaijani education system.
Keywords: Azerbaijan -- Languages; Azerbaijan -- Education -- 21st century; Language and education -- Azerbaijan; Cultural identity; Education